Implementasi Syari’at Islam di Aceh: Studi Kasus Peranan Da’i Perbatasan di Kabupaten Aceh Tamiang - Abidin Nurdin; Muslim Zainuddin; Salman Abdul Muthalib; Fakhrurrazi Fakhrurrazi (Al-Adalah: Jurnal Hukum dan Politik Islam, 2021)
This study aims to discuss the implementation of Islamic law in Aceh, especially regarding the role of border preachers in Aceh Tamiang District, Aceh Province. This research is a study of the sociology of law or empirical law that discusses the law in reality or the reality in people's lives. There are two data collection techniques used, namely literature review and in-depth interviews. This study concludes that the border preacher is a program of the Islamic Shari'ah Service which aims to support the implementation of Islamic law in border areas and remote areas in Aceh. Namely in the regions, Singkil, South Aceh, Subulussalam, Simeulu, Southeast Aceh, and Aceh Tamiang. Especially in Aceh Tamiang, the border preacher has carried out his duties and functions well, namely carrying out religious recitation activities, recitation of al-Qur’an education park, strengthen aqidah and maintaining religious harmony in society. Thus, in the context of the sociology of Islamic law applied in Aceh, it has a positive impact on the community in the sense that people are religiously obedient, their religious knowledge increases, strong aqidah and religious life becomes harmonious.